PENGENDALIAN INTERNAL SEBAGAI TOOLS SISTEM PENGELUARAN KAS PADA CAFÉ JOE NATHAN DI JAKARTA SELATAN - Herlina, Herlina; Purnomo, D; Winarti, Euis; Purwitasari, Maria Evy; Minggu, Minggu (JURNAL LENTERA AKUNTANSI, 2025)
This article discusses the internal control system as a tool for controlling the cash disbursement system at Café Joe Nathan. The research methodology used is a qualitative method with a field study approach to collect data directly through the process of recording activities occurring in the field to prepare a research report. Based on the data obtained from the field study, interviews, field notes, and documentation, the report is then compiled. This research discussion covers the main elements of internal control: organization, authorization system, recording procedures and sound practices, as well as the risks faced in the cash receipts system, as well as procedures that can be implemented to ensure the system runs safely and effectively. The implementation of internal controls in the cash receipts system is expected to provide insight for Café Joe Nathan's management to strengthen their financial system and increase stakeholder trust in the company. The research results indicate that the Internal Control System (ISC) implemented by Café Joe Nathan is sound, with a separation of functions, an authorization system and recording procedures, and the implementation of sound practices such as same-day recording. The organizations involved in the Cash Disbursement System are the production department, operations department, and accounting department. Regular evaluations of cash disbursement reports and internal audits are conducted to maintain data accuracy and prevent misuse.